2013
DOI: 10.1200/jco.2012.45.2615
|View full text |Cite
|
Sign up to set email alerts
|

Lumpectomy Plus Tamoxifen With or Without Irradiation in Women Age 70 Years or Older With Early Breast Cancer: Long-Term Follow-Up of CALGB 9343

Abstract: With long-term follow-up, the previously observed small improvement in locoregional recurrence with the addition of radiation therapy remains. However, this does not translate into an advantage in OS, distant disease-free survival, or breast preservation. Depending on the value placed on local recurrence, Tam remains a reasonable option for women age ≥ 70 years with ER-positive early-stage breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
695
0
20

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 1,033 publications
(746 citation statements)
references
References 23 publications
31
695
0
20
Order By: Relevance
“…101,103,104 It is much smaller than the 7.5% margin in the ELIOT trial 105 and lower than the difference considered 'acceptable' by the CALGB (5% difference) 11 and Post-operative Radiotherapy In Minimum-risk Elderly (PRIME) II (3% difference) 106 studies. At this boundary, TARGIT was non-inferior to EBRT (P non-inferiority < 0.00001).…”
Section: Non-inferiority For Local Recurrencementioning
confidence: 99%
See 2 more Smart Citations
“…101,103,104 It is much smaller than the 7.5% margin in the ELIOT trial 105 and lower than the difference considered 'acceptable' by the CALGB (5% difference) 11 and Post-operative Radiotherapy In Minimum-risk Elderly (PRIME) II (3% difference) 106 studies. At this boundary, TARGIT was non-inferior to EBRT (P non-inferiority < 0.00001).…”
Section: Non-inferiority For Local Recurrencementioning
confidence: 99%
“…For example, the only other trial of IORT -the ELIOT trial 35 -was set up with the assumption that a difference of 7.5% in local recurrence between the experimental and the control groups would result in the two treatments being considered as equivalent. The Cancer and Leukemia Group B (CALGB) study 11 found that there was a 7% difference in local recurrence when radiotherapy was omitted in low-risk (T1N0) patients aged > 70 years and concluded that this difference was not significant. Furthermore, two patient preference studies conducted in parallel with the main trial have also corroborated that, given the convenience of a single treatment session, the median increase in local recurrence that patients would be ready to accept is 2.5%.…”
Section: Non-inferiority For Local Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…The loco-regional recurrence rate in CALGB 9343 trial was 1% in irradiated (RT+) and 4% in non-irradiated patients (RT-) at 5 years, p=0.001 [16] and the difference had increased (2% RT+, 9% RT-) at a median follow-up of 10.5 years [17].…”
Section: Role Of Radiotherapy (Rt) After Breast Conservative Surgmentioning
confidence: 99%
“…Results showed a very low axillary recurrence rate at a median follow-up of 12.6 years -none in those who underwent ALND and in those who did not undergo ALND but received tamoxifen plus WBRT, but 3% in those on tamoxifen alone [17].…”
mentioning
confidence: 98%